Burnout Syndrome in the Era of Electronic Health Records: A Scoping Review - Silva, Marla Ariana; Tavares, LaÃs Oliveira de Moraes; Amaral, Ana Clara Morais; Xavier Junior, Gesner Francisco; Oliveira, Valéria Conceição de; Gontijo, TarcÃsio Laerte; Cavalcante, Ricardo Bezerra; Carvalho, Dárlinton Barbosa Feres; Guimarães, Eliete Albano de Azevedo (Revista Cubana de Información en Ciencias de la Salud, 2024)
Burnout Syndrome is characterized as a psychosocial phenomenon, resulting from the inability to adapt and cope with stressors to which the professional is exposed. The use of technological innovations such as the Electronic Health Record has been associated as one of the potential factors for Burnout Syndrome. To analyze the scientific evidence on Burnout Syndrome in Electronic Health Records use. This is a scoping review study conducted in the PubMed, Scopus, Embase, WoS and Cochrane databases. Data collection took place in February and March 2021 using the following descriptors: Burnout, Electronic Health Records, Health Information Systems, Occupational Burnout, Professional, Psychological Distress. Of the 996 studies found, 44 were selected for full reading, of which 21 articles made up the final sample. The studied population was predominantly made up of nurses and doctors who worked in primary care and hospitals. It was observed that exhaustion, stress, emotional exhaustion, dissatisfaction and depersonalization were the most predominant stressors related to the use of Electronic Health Records. Regarding the level of evidence of the articles, 95% of them presented level IV and only 5% level III. Electronic Health Records have contributed more agility and efficiency to their users, although there are still divergent points that need to be reviewed in order to help reduce physical and mental exhaustion in nurses and physicians as a result of this software.